„Post-Truth“ – Headers and the Content of Russian Internet Resources - Arseniev, Svetoslav (Research Papers, 2020)
The article considers the interpretation of the term „post-truth“ in Russian Internet sources. The prerequisites are outlined for the appearance of this phenomenon, the terms connected with it, the environment, inside which it exists, the correspondence between the contents in the titles or the contents of the term „post-truth“ of the listed facts and their interpretation.Some questions are also considered, referring to the techniques of manipulation. It has been shown that it is not the lack of information, but rather „the per-saturation" with information could lead to formation of „unrealistic“ and in its context even „untrue“ reading of a given specific phenomenon.
Keywords: Russia; Post-truth; Internet resources